The Mutualistic Side of Wolbachia–Isopod Interactions: Wolbachia Mediated Protection Against Pathogenic Intracellular Bacteria - Braquart-Varnier, Christine; Altinli, Mine; Pigeault, Romain; Chevalier, Frédéric D.; Grève, Pierre; Bouchon, Didier; Sicard, Mathieu (Frontiers in Microbiology, 2015)
Wolbachia is a vertically transmitted endosymbiont whose radiative success is mainly related to various host reproductive manipulations that led to consider this symbiont as a conflictual reproductive parasite. However, lately, some Wolbachia have been shown to act as beneficial symbionts by protecting hosts against a broad range of parasites. However this protection has been mostly demonstrated in artificial Wolbachia-host associations between partners that did not co-evolved together. Here, we tested in two terrestrial isopod species Armadillidium vulgare and Porcellio dilatatus whether resident Wolbachia (native or non-native) could confer protection during infections with Listeria ivanovii and Salmonella typhimurium and also during a transinfection with a Wolbachia strain that kills the recipient host (i.e. wVulC in P. dilatatus). Survival analyses showed that (i) A. vulgare lines hosting their native Wolbachia (wVulC) always exhibited higher survival than asymbiotic ones when infected with pathogenic bacteria (ii) P. dilatatus lines hosting their native wDil Wolbachia strain survived the S. typhimurium infection better, while lines hosting non-native wCon Wolbachia strain survived the L. ivanovii and also the transinfection with wVulC from A. vulgare better. By studying L. ivanovii and S. typhimurium loads in the hemolymph of the different host-Wolbachia systems, we showed that (i) the difference in survival between lines after L. ivanovii infections were not linked to the difference between their pathogenic bacterial loads, and (ii) the difference in survival after S. typhimurium infections corresponds to lower loads of pathogenic bacteria. Overall, our results demonstrate a beneficial effect of Wolbachia on survival of terrestrial isopods when infected with pathogenic intracellular bacteria. This protective effect may rely on different mechanisms depending on the resident symbiont and the invasive bacteria interacting together within the hosts.